2020
DOI: 10.1111/cod.13599
|View full text |Cite
|
Sign up to set email alerts
|

Mask‐induced contact dermatitis in handling COVID‐19 outbreak

Abstract: An otherwise healthy 23-year-old woman presented with facial symmetrical erythema and slight itching lasting 4 days. Symptoms developed after wearing a KN95 (FFP2 equivalent) mask for 2 days to prevent contracting SARS-CoV-2. One day before, the patient had consulted the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 5 publications
0
46
2
1
Order By: Relevance
“…Other identified contact allergens include polyurethanes (toluene-2,4-diisocyanate, 4,4′-diaminodiphenylmethane, hexamethylene diisocyanate) and formaldehyde-releasing preservatives (formaldehyde, 2-bromo-2-nitropropane-1,3-diol) [97,98]. Trace amounts of formaldehyde can be present in polypropylene masks as a degradation by-product [99].…”
Section: Allergic Contact Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…Other identified contact allergens include polyurethanes (toluene-2,4-diisocyanate, 4,4′-diaminodiphenylmethane, hexamethylene diisocyanate) and formaldehyde-releasing preservatives (formaldehyde, 2-bromo-2-nitropropane-1,3-diol) [97,98]. Trace amounts of formaldehyde can be present in polypropylene masks as a degradation by-product [99].…”
Section: Allergic Contact Dermatitismentioning
confidence: 99%
“…Trace amounts of formaldehyde can be present in polypropylene masks as a degradation by-product [99]. A polyurethane sponge lined within a KN95 facemask was implicated in ACD involving the nasal bridge and zygomatic arches [97]. Retro-auricular ACD due to facemask ear loops composed of different materials including thermoplastic elastomer, rubber, and latex has been described [96].…”
Section: Allergic Contact Dermatitismentioning
confidence: 99%
“…• In the case of a suspected ACD, test the baseline series (eg, European baseline series), 28 which contains the most common allergens that may cause mask-induced ACD such as thiuram mix, mercapto mix, fragrance mix I and II, isothiazolinones, formaldehyde and formaldehyde releasers 7,8,10 ; test other allergens in addi-…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…13 However, the prolonged mask contact could increase the ACD "burden" in the coming months. 10 It has been reported that up to 97% of health care workers showed skin lesions related to enhanced protection measures, mainly affecting the nasal bridge, cheek and forehead in addition to the hands. 14,15 The most common symptoms were dryness and tightness, whereas the most common sign was desquamation.…”
mentioning
confidence: 99%
“…In this study, a hydrophobic mask coating was developed with wetting resistance and self-cleaning features. A simple protocol is presented wherein a flexible, stable, reusable, and economical C-PU mask is subjected to environmental engineering processes ( Allison et al, 2020 , Xie et al, 2020 ). This study conducted fundamental research into the development of hydrophobic and anti-droplet masks.…”
Section: Introductionmentioning
confidence: 99%